2019
DOI: 10.1007/s11151-019-09699-1
|View full text |Cite
|
Sign up to set email alerts
|

New Business Formation and Incumbents’ Perception of Competitive Pressure

Abstract: A b s t r a c tWe investigate the relationship between new business formation and the level of competitive pressure perceived by manufacturing incumbent establishments. The perceived pressure of competition is stronger the higher the level of entries in the respective industry. This relationship holds not only for start-ups located in the same region of the incumbent, but also for start-ups across all regions of Germany. The productivity level of an incumbent moderates the extent of the perceived competitive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In order to further verify the fitting degree between the conceptual model and the actual data, the structural equation model was used to verify the hypothesis test.According to the fitting results of the initial model, the covariance relationship between the increased residuals for the parameter paths with MI>3.84 was analyzed using the residuals output from the structural equation model [32], and the model was revised and determined for the initial model.After correction, the structural equation model shown in Fig. 1 is formed.Fitting was performed by importing data, and the results are shown in Table 7.The fitting results showed that the value of 2 was 3380.516 (df=1378), and the value of 2/df was 2.453, which was less than 3; RMSEA=.067, less than 0.08; The values of NFI, TLI, CFI, and IFI were .916, .921, .901, and .902, respectively, all higher than 0.9, indicating that the model had a good fitting effect.There were a total of 18 paths between variables.…”
Section: Hypotheses Testingmentioning
confidence: 99%
“…In order to further verify the fitting degree between the conceptual model and the actual data, the structural equation model was used to verify the hypothesis test.According to the fitting results of the initial model, the covariance relationship between the increased residuals for the parameter paths with MI>3.84 was analyzed using the residuals output from the structural equation model [32], and the model was revised and determined for the initial model.After correction, the structural equation model shown in Fig. 1 is formed.Fitting was performed by importing data, and the results are shown in Table 7.The fitting results showed that the value of 2 was 3380.516 (df=1378), and the value of 2/df was 2.453, which was less than 3; RMSEA=.067, less than 0.08; The values of NFI, TLI, CFI, and IFI were .916, .921, .901, and .902, respectively, all higher than 0.9, indicating that the model had a good fitting effect.There were a total of 18 paths between variables.…”
Section: Hypotheses Testingmentioning
confidence: 99%
“…Although there is a certain consensus regarding the role of entrepreneurship in economic growth (Audretsch 2007;Audretsch, Keilbach, and Lehmann 2006;Baumol, Litan, and Schramm 2007;Changoluisa and Fritsch 2019;Fritsch and Changoluisa 2017;Kirzner 1973;Schumpeter 1934), there is no consensus on the exact meaning of entrepreneurship and the definition of entrepreneurs (Parker 2004). According to Peneder (2009), it is possible to define and identify entrepreneurs according to their function, behavior and occupational status.…”
Section: Dependent Variablementioning
confidence: 99%
“…In the light of this view, competition will be perceived by managers, and the managers' cognitions of competitive environment can measure the degree of competition. According to the industrial organization view, some firms with similar characteristics can be clustered in smaller groups, and there are closer links between such firms in the same group (Zucchini et al, 2019;Changoluisa and Fritsch, 2020). On one hand, the complexity of internal and external environment forces managers to pay more attention to some firms with similar business or product, and then construct a portfolio of competitors (Medhi and Allamraju, 2022).…”
Section: Introductionmentioning
confidence: 99%